Biology, ecology and management of white wax scale, Ceroplastes destructor Newstead (Hemiptera: Coccidae), on citrus and syzygium - Wakgari, Waktola (Waktola Muleta) (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--University of Stellenbosch, 2000.